First Seizure in a 16-Year-Old Girl Associated With Tuberous Sclerosis Complex: A Case Report - Sari, Cindy Permata; Sumada, I Ketut; Yuliani, Desie; Jayanthi, Ni Made Kurnia Dwi (Acta Neurologica Indonesia, 2026)
Introduction : Tuberous sclerosis complex (TSC) is a rare autosomal dominant disorder causing benign tumors in multiple organs. It affects 1 in 6,000 births globally, with a prevalence of 1 in 20,000. However, data in Indonesia remain limited. TSC is marked by seizures, developmental delays, and distinct skin lesions. Case Report : A 16-year-old girl experienced her first seizure. She had no prior TSC diagnosis. Clinical examination revealed generalized tonic clonic seizure, cognitive impairment, and distinctive skin features, including hypomelanotic macules, angiofibromas, a shagreen patch, and non-renal hamartomas. A non-contrast head CT scan confirmed multiple punctate calcifications in the periventricular regions of both lateral ventricles, consistent with TSC. Diagnosis was delayed until her first seizure. Discussion : Diagnosing TSC is challenging. Seizures are often the first noticeable sign. Cognitive delays highlight the need for early screening in children with learning difficulties, particularly when TSC symptoms are present. Limited awareness among healthcare providers and the public contributes to delayed diagnosis. Mutations in TSC1/TSC2 genes disrupt the mTOR pathway, leading to abnormal cell growth and hamartoma formation, increasing seizure risk. Raising awareness is crucial for early detection and timely intervention. Conclusion : TSC often goes undiagnosed until adolescence due to limited awareness and missed early signs. Seizures are a key warning sign requiring evaluation, making TSC a crucial consideration in new-onset seizures, particularly with characteristic skin or brain findings. Early detection and comprehensive care are essential for preventing complications and improving quality of life.